"Silver" product design: Product innovation for older people - Cornelius Herstatt; Florian Kohlbacher; Patrick Bauer (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2011)
Aging populations challenge companies across different countries and industries to respond to the changing needs, demands and expectations of their growing shares of older customers. This opens room for improving or developing innovations - products as well as services - that correspond to the diverse expectations. New product development for older customers or 'Silver' product design is one way to approach the 'silver' market - without explicitly excluding younger customers. Research in this field is still in its infancy. Silver product design focuses on individual autonomy, representing an elementary aspect of good life, disappearing in a more or less continuous manner over the life cycle of a human being. Offering solutions that will allow people to maintain or recover autonomy and to use products and services in an independent manner therefore seems to be a promising avenue for companies innovating across different industries. The general concept of autonomy can be perceived as a boundary-spanning argument and a common denominator for starting development initiatives leading to innovations targeting the silver market. Cross-case analysis based on four different product innovations addressing typical needs of older people are used to present how firms in different industrial contexts and user-settings address such needs, which have their roots in a need to stay autonomous and independent. Technological, marketing and strategy-related observations as well as communalities and differences of the cases are being discussed and very first implications for managing the front end of silver product development sketched.
Keywords: 650; Demographic change; aging; older users; silver market; innovation management; silver product design; individual autonomy